Biophysical effects in off‐resonant gold nanoparticle mediated (GNOME) laser transfection of cell lines, primary‐ and stem cells using fs laser pulses. Issue 8 (9th October 2014) - Schomaker, Markus; Killian, Doreen; Willenbrock, Saskia; Heinemann, Dag; Kalies, Stefan; Ngezahayo, Anaclet; Nolte, Ingo; Ripken, Tammo; Junghanß, Christian; Meyer, Heiko; Escobar, Hugo Murua; Heisterkamp, Alexander
Abstract : Gold nanoparticle mediated (GNOME) laser transfection is a powerful technique to deliver small biologically relevant molecules into cells. However, the transfection of larger and especially negatively charged DNA remains challenging. The efficiency for pDNA was 0.57% using parameter that does not influence the endo‐ and exogenous DNA. In order to gain a deeper understanding of the actual molecule uptake process, the uptake efficiency was determined using molecules of different sizes. It was evaluated that uncharged dextran molecules (2000 kDa) were delivered with an efficiency of 68%. The intracellular distribution of injected molecules was visualized and larger molecules were primary found in the cytoplasm. Patch clamp measurements suggested a permeabilization time up to 15 minutes. The uptake efficiency depended on the size and charge of the molecule to deliver as well as the cell size. A minor role for transfection plays the cell type since primary stem cells were successfully transfected.The perforation efficiency of semi‐adherent and suspension cells is influenced by the cell and molecule size. Abstract : Gold nanoparticle mediated (GNOME) laser transfection is a powerful technique to deliver small biologically relevant molecules into cells. However, the transfection of larger and especially charged molecules like plasmid DNA remains challenging. To get a deeper understanding of the uptake process, the biophysical mechanisms involved in GNOME laser transfection were investigated. Furthermore, successful transfection of stem cells was performed providing an alternative method for the development of molecular medical approaches.